Rural-to-Urban Migration in Nepal: Causes, Trends, and Effects on Rural Development - Sharma, Laxmi (Rural Development Journal, 2026)
Nepal's rural-to-urban migration has increased as a result of social, economic, and environmental issues, significantly affecting rural development. The main causes of this migration include declining agricultural productivity in rural areas, a lack of education, and a lack of employment opportunities. While rural areas experience socioeconomic difficulties and a labor shortage, the trend speeds up urban population growth, particularly in provinces like Bagmati. Increased remittances, altered income levels, lifestyle modifications, and dependence on urban infrastructure are some of the effects. Despite such barriers, migration is nevertheless an instrument for strengthening rural populations' overall standard of living. This study examines Nepal's causes, current migration trends, and socioeconomic effects, focusing on the relationship between urban and rural migration. The study emphasizes that in order to reduce negative consequences and promote balanced growth, integrated rural-urban development policies are necessary.